Hubungan kondisi tutupan terumbu karang dengan kepadatan megabentos di perairan Pulau Talam Kabupaten Tapanuli Tengah Provinsi Sumatera Utara - Alfeus Jhonson Armada H; Thamrin Thamrin; Irvina Nurrachmi (Jurnal Zona, 2022)
This research was conducted in March 2022 in the waters of Talam Island, Central Tapanuli Regency, North Sumatra Province. This study aims to determine the relationship between coral cover and the density of megabenthos in the Talam Island area. The method used in this research is a survey method. Coral cover data were collected using the LIT (Line Intercept Transect) method and megabenthos data were collected using the BBT (Benthos Belt Transect) method. Observations were made at three station points with each station with a depth of 4 meters, 6 meters and 8 meters. The results showed that Talam Island had a good percentage of coral cover with an average of 54.74%. The highest density of megabenthos was Tridacninae found at each station, while the lowest density was Acanthaster planci. The overall megabenthos density has an average of 10.033 ind/ha. Coral reef cover relationship has an influence on the density of megabenthos, there is a strong positive effect on economic megabenthos and a strong negative on non-economic megabenthos.